Beliefs Associated with Intention to Use PrEP among Cisgender U.S. Women at Elevated HIV Risk - Teitelman, Anne M. (Arch Sex Behav, 2020)
Women comprise 19% of those newly diagnosed with HIV in the United States. There is a wide gap between recommended use of pre-exposure prophylaxis (PrEP) and actual uptake among women who are eligible for PrEP. In order to identify women’s beliefs and intentions about starting PrEP, a survey, informed by the Reasoned Action Approach, was administered to 160 cisgender PrEP-eligible women, ages 18–55, in Philadelphia and New York City. The mean age was 40.2 years (SD = 11.78), 44% had completed high school, 75% were unemployed and 85% experienced financial instability in the past 3 months. Multivariate linear regression analyses identified sets of behavioral and normative beliefs associated with intention to start PrEP in the next 3 months. Behavioral beliefs reflected views about PrEP benefits such as preventing HIV and normative beliefs reflected perceptions of support or lack thereof from others including partners, friends, mother, and children. These findings can be used to inform interventions to foster greater PrEP uptake among women.